Recurrent insulin-induced hypoglycemia induces AngII and COX2 leading to renal (pro)renin receptor expression and oxidative stress - Alanazi, Wael; Uddin, Mohammad; Fakhruddin, Selim; Jackson, Keith (International Journal of Medicine, 2017)
Background: Recurrent insulin-induced hypoglycemia (RIIH) is an avoidable consequence in the therapeutic management of diabetes mellitus. RIIH has been implicated in causing hypertension through an increase in renal and systemic AngII production.Objective: The present study was performed to assess the hypothesis that chronic insulin treatment enhances AngII and COX2 formation which in turn increases (pro) renin receptor (PRR) expression and NADPH oxidase-mediated oxidative stress, leading to renal and cardiac injury.Methods: The present studies were conducted in Male Sprague Dawley rats treated with daily subcutaneous injections of 7u/kg insulin or saline for 14 days. On the 14th day, surgery was performed for treatment infusion (captopril 12mg/kg, NS398 0.3mg/kg or vehicle), and renal interstitial fluid sample and urine collections for biomarker measurements. At the end of the experiments, kidneys and hearts were harvested to evaluate PRR and NOX2 (NADPH oxidase subunit) expression and oxidative stress.Results: We found that RIIH enhanced AngII and COX2 activity, leading to renal PRR expression and NADPH oxidase-induced oxidative stress in the heart and kidney. 8-isoprostane was evaluated as a renal biomarker of oxidative stress, which was induced in insulin treated animals and modulated by captopril and NS398. In addition, there was a slight increase in NGAL, a urinary biomarker of acute kidney injury (AKI), in insulin treated animals when compared to control.Conclusion: These results demonstrate that RIIH induces renal PRR expression and oxidative stress through increasing AngII and COX2 in the heart and kidney, leading to end-organ damage.